Acquired and congenital halo nevi with bifocal vitiligo. - Milano, A.; Ciampo, L. (European Journal of Pediatric Dermatology, 2009)
A baby girl was first observed due to a congenital melanocytic nevus of the left hip (Fig. 3) and was thus included in a prospectic study of clinical monitoring with a planned biannual examination. When aged 5, she presented inflammation and white halo around an acquired nevus of the left cheek (Fig. 1). Dermoscopy (box of Fig. 1) showed only inflammation. At the age of 6, there was complete regression of the acquired nevus with minimal residual atrophy (Fig. 2), testified also by dermoscopy (box of Fig. 2) and simultaneously regression with halo, but without inflammation, of the congenital melanocytic nevus of the hip (Fig. 4). At the age of 7 vitiligo appeared with a focus on the right upper eyelid and another one level with two adjacent eyelashes of the left upper eyelid (Fig. 5), with persistent atrophic scar of the acquired halo nevus and depigmentation of the congenital melanocytic nevus (Fig. 6, 7). The final diagnosis was acquired and congenital halo nevi with bifocal vitiligo.